Pijat Common Cold pada Bayi dan Balita untuk Mengatasi Batuk Pilek di Posyandu Balita di Dusun Blater Lor, Desa Jimbaran - Dian Ayu Tias Pradani; Oktaviani, Ismi; Jumiati; Hapsari Windayanti (Universitas Ngudi Waluyo, 2023)
Babies are weak individuals and require an adaptation process. Every baby must be able to go through a physiological adaptation process which consists of the cardiovascular, respiratory system, hematopoiesis system, metabolism, body temperature, digestive tract system, endocrine glands, immunoglobulin system, glucose metabolism, integumentary and reproductive systems. Doing a common cold massage which consists of stages of baby cough and cold massage which consists of the following movements toward bridge nose & under the cheek bone, cheek rain drop, open book, butterfly, toby top intercostal, chest rain drop, positioning the baby face down, back and forth, sweeping neck to bottom, sweeping neck to feet, back circle, back rain drop, pitching and relaxation. Counseling on Common Cold Massage for Babies and Toddlers as an Effort to Treat Coughs and Colds in the Blater Lor Hamlet Area, Jimbaran Village, Bandungan District, Semarang Regency, which was attended by 13 respondents from mothers who have babies. Implementation of Community Service will be carried out on Tuesday, November 21 2023 starting at 09.00 – 11.30 WIB offline, using the method of introduction first, then completing the pre-test, then presenting the material and continuing with a common cold massage demonstration with 13 stages, then a question and answer process then fill in the post test and finally cover. Counseling participants understand and understand how to do Common Cold Massage to Treat Coughs and Colds in Babies and Toddlers and communication can be established between both the proposing team and the mothers doing the counseling. There is an increase in the knowledge and skills of mothers, which can be seen from the percentage data from 55% (pretest) to 100% (posttest). It is hoped that mothers can practice common cold massage at home independently when their children have coughs and colds. Abstrak Bayi merupakan individu yang lemah dan memerlukan proses adaptasi. Setiap bayi harus dapat melalui proses adaptasi fisiologis yang terdiri dari kardiovaskuler, sistem pernafasan, sistem hematopoiesis, metabolisme, suhu tubuh, sistem traktus digestivus, kelenjar endokrin, sistem imunoglobulin, metabolisme glukosa, sistem integumen dan reproduksi. Melakukan pijat common cold yang terdiri dari tahapan pijat bayi batuk pilek yang terdiri dari gerakan berikut melakukan gerakan toward bridge nose & under the cheek bone, cheek rain drop, open book, butterfly, toby top intercostal, chest rain drop, memposisikan bayi telungkup, back and forth, sweeping neck to bottom, sweeping neck to feet, back circle, back rain drop, pitching dan relaksasi. Penyuluhan Pijat Common Cold Pada Bayi dan Balita Sebagai Upaya Mengatasi Batuk Pilek di Wilayah Dusun Blater Lor, Desa Jimbaran, Kecamatan Bandungan, Kabupaten Semarang yang diikuti oleh 13 responden Ibu yang memiliki bayi. Pelaksanaan Pengabdian Masyarakat dilakukan Hari Selasa, 21 November 2023 mulai pukul 09.00 – 11.30 WIB secara luring (offline), dengan metode dengan perkenalan terlebih dahulu selanjutnya pengisian pre test, kemudian pemaparan materi dan dilanjutkan demonstrasi pijat common cold dengan 13 tahapan, berikutnya proses tanya jawab kemudian pengisian post test dan terakhir penutup. Peserta penyuluhan mengerti dan memahami cara melakukan Pijat Common Cold Untuk Mengatasi Batuk Pilek pada Bayi dan Balita dan bisa terjalin komunikasi baik tim pengusul dan para ibu yang melakukan penyuluhan. Terdapat peningkatan pengetahuan dan keterampilan ibu-ibu, yang dilihat dari data presentase baik 55% (pretest) menjadi 100% (post test). Diharapkan ibu-ibu dapat mempraktikkan pijat common cold dirumah secara mandiri saat anaknya mengalami batuk dan pilek.